It began in Copenhagen : junctions in 300 years of Indian-Danish relations in Christian mission - Oommen, George; Iversen, Hans, 1948- (Delhi : Indian Society for Promoting Christian Knowledge, 2005)
Contributed research papers.
Includes bibliographical references and indexes.
Keywords: Missions, Danish -- India -- History